Race and the Mona Lisa: Reflecting on Antiracist Teaching Practice. Issue 3 (3rd July 2019) - Khasnabis, Debi; Goldin, Simona; Perouse-Harvey, Ebony; Hanna, Margaret O.
Abstract: We report on multicultural education pedagogies that support teacher candidates in enacting antiracist teaching practice. These pedagogies draw from the experience of a 12-year-old child in an art class assignment that involved race and the Mona Lisa. We highlight the integration of practice with reflection as we link structured opportunities to practice the work of partnering with families—learning with and from them in dialog across racial issues—with opportunities to reflect on this practice.